Correlation of laws and subordinate normative legal acts in financial relations regulation - Дмитрик, О. О. (Problems of legality, 2014)
According to the legal force, financial normative legal acts are divided into laws and secondary legislation. Not secondary legislation, but financial laws – regulations emanating from the highest legislative body - the parliament, which are endowed with a higher legal force, should be the main source of law in financial sector of the state and local government activity. All other subordinate legislation must be issued solely on the basis of law and must be consistent with it. An essential requirement for any financial regulatory act, along with necessity of adoption under the competence of public body, strict certainty, etc., should be a requirement of its strict conformity with acts of the highest authorities, compulsory passing through the hierarchy principle, by using which unity of numerous acts and their coordinated action is achieved in law.